(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aims to describe the current status of knowledge and preventive practices regarding dermatophytosis among patients attending the Department of Dermatology, Thai Nguyen University of Medicine and Pharmacy Hospital in 2025, and to analyze factors associated with preventive practices. Methods: A cross-sectional descriptive study was conducted among 402 patients aged 18 years and older who attended the Department of Dermatology, Thai Nguyen University of Medicine and Pharmacy Hospital in 2025. Data were collected through face-to-face interviews using a structured questionnaire. Data were entered and analyzed using Epidata 3.1 and SPSS 27.0. Results: The majority of patients had heard of dermatophytosis (91.8%) and demonstrated relatively good knowledge regarding sources of infection, predisposing factors, and clinical manifestations. However, knowledge related to treatment and prevention was limited; only 68.4% knew that antifungal medications are required, and 52.2% were aware that topical corticosteroid-containing products should not be used. Regarding practices, 93.3% reported not sharing clothing, but 28.4% still shared personal items, and 61.2% self-medicated when infected. Patients aged over 40 years had a significantly higher proportion of inadequate preventive practices compared to those aged 18–40 years (p < 0.05) Conclusion: Knowledge and preventive practices regarding dermatophytosis among patients remain inadequate, particularly in terms of medication use and control of transmission sources. Targeted health education and communication programs are needed, focusing on preventive practices, rational use of antifungal medications, and prevention of recurrence, especially among older patients.